Unlocking Minds: The Promising Horizon of Cognitive Behavior Therapy in Pakistan - Ahmed, Bashir; Ahmad, Waleed (Journal of Gandhara Medical and Dental Science, 2023)
Cognitive Behavior Therapy (CBT) has come a long way since its inception in the 1960s. The approach has effectively treated various psychological disorders, from anxiety and depression to post-traumatic stress disorder and substance abuse. However, as we move further into the 21st century, the future of CBT is poised to undergo significant innovation. Cognitive Behavior Therapy (CBT) is evolving rapidly, and its future holds exciting new developments. Emerging trends in CBT include the use of digital and mobile applications to increase access to mental health services and the development of personalized treatment plans based on an individual’s unique needs. These transdiagnostic approaches treat underlying mechanisms that cut across different disorders, the integration of new technologies, and the emphasis on self-help strategies. These innovative approaches offer promising new ways to treat mental health disorders more effectively and efficiently and are likely to shape the future of CBT.1 Here briefly discuss the emerging trends that could shape the future of CBT: Digital and Mobile Applications; with the rise of telehealth and digital mental health platforms, CBT is being integrated into mobile and online applications. These platforms enable greater access to mental health services, reaching individuals who may not have access to traditional in-person therapy. Personalized Treatment; CBT is moving beyond a one-size-fits-all approach. Customized treatment plans can be developed using assessment data and digital monitoring tools. This approach considers an individual’s unique circumstances, symptoms, and treatment preferences to create a more effective and targeted treatment plan. Transdiagnostic Approaches: In the past, CBT has primarily focused on treating specific disorders. However, the transdiagnostic approach is gaining attraction, emphasizing treating underlying mechanisms that cut across different disorders. This approach may enable the treatment of comorbid conditions more efficiently and effectively.2 Incorporating New Technologies; The use of new technologies, such as virtual reality and brain stimulation techniques, has shown promise in treating a range of psychological disorders.3 Incorporating these tools into CBT may offer more effective treatment options for individuals who are unresponsive to traditional therapies. Emphasizing Self-Help Strategies; CBT’s future may rely on empowering individuals to control their mental health through self-help strategies. By utilizing mobile applications, online resources, and telehealth, individuals may gain access to resources that can help them manage their symptoms more effectively. The future of Cognitive Behavior Therapy (CBT) in Pakistan is bright, as the country is experiencing a growing demand for mental health services. There is a need for effective, evidence-based treatments like CBT, which have demonstrated efficacy in treating various psychological disorders. However, several challenges need to be addressed to increase the availability and accessibility of CBT in Pakistan.4 One of the major challenges is the shortage of mental health professionals, particularly those trained in CBT. To address this issue, there is a need for increased investment in mental health education and training and initiatives to attract and retain mental health professionals. Another challenge is the cultural context in which CBT is delivered in Pakistan. Cultural sensitivity and adaptation of CBT are crucial to its success, and this can be achieved through collaboration with local experts and stakeholders to tailor the approach to the local context. To fill the gap in CBT training, a 6-month postgraduate certificate training program was started in 2017 at Khyber Medical College Peshawar, affiliated with Khyber medical university Peshawar. This training attracted mental health professionals from all over the country, and so far, about 100 mental health professionals (psychiatrists and psychologists) have been trained in CBT. CBT training has been further enhanced, and a one-year postgraduate diploma training program was started in 2022 at Bashir Psychiatric Hospital and Institute in collaboration with Gandhara University Peshawar. This training program covers the treatment of a broad range of psychiatric disorders, including depression, various anxiety states such as panic anxiety, social anxiety, post-traumatic stress disorder (PTSD), obsessive-compulsive disorder (OCD), conversion disorder, personality disorder, drug addiction and psychosis. In conclusion, using technology and telehealth can greatly enhance the availability and accessibility of CBT in Pakistan. With the increasing adoption of digital technologies in the country, mobile applications and online resources can expand the reach of mental health services to underserved populations.